Excavations at Qasrij Cliff and Khirbet Qasrij. With contributions by Dominique Collon and appendices by R.K. Uprichard, M.S. Tite, I.C. Freestone and M.J. Hughes - Curtis, John (1989)
= Saddam Dam Report 10